Utilization of T-O-E Framework in IoT for Food Quality Management: The Role of Perceived Risk in the Industry - Agnes Amaranggana Anindita; Yolanda Masnita Siagian; Wahyuningsih Santosa (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to analyze factors within the Technological-Organizational-Environmental (T-O-E) framework influencing QM IoT adoption in the food industry, with perceived risk as a moderating variable. The population in this study are employees who work in the top eight food industry companies with the largest retail sales value in Indonesia. The research sample was selected using purposive sampling method of 186 respondents. Data analysis was conducted using partial least squares (PLS), which is a structural equation modeling (SEM). Based on the statistical test result, it was found that relative advantage, innovative capability, executive support, value chain partner pressure, and competitor pressure have a significant positive effect on QM IoT adoption intention. At the same time, complexity has a significant negative effect on QM IoT adoption intention. Perceived risk positively as a moderator that strengthens the influence between innovative capability, executive support, value chain partner pressure, and competitor pressure and QM IoT intention adoption. Meanwhile, perceived risk does not significantly as a moderator on relative advantage and complexity. The practical implications of these findings provide direction to decision-makers, policymakers, technology practitioners, and researchers in developing strategies to support the successful adoption of QM IoT.